718 DIFFERENCES BETWEEN INTRACORPOREAL AND EXTRACORPOREAL GASTRIC TUBE RECONSTRUCTION AFTER ESOPHAGECTOMY: IS THERE A BETTER WAY?. (17th September 2021) - Takeda, F; Aissar Sallum, R; Ribeiro, U; Cecconello, I; Nahas, S
Abstract: Introduction: Esophagectomy remains good option to curative intent for esophageal carcinoma. However, quality of life for post-operative symptoms such as reflux, gastric emptying delayed and dysphagia is on debate. Some studies advocate relations between those symptoms to gastric tube conformation and discrepancies between intra and extracorporeal gastric tube construction. We aimed to analyze differences between both methods. Methods: During 2014–2020, patients underwent to esophagectomy by thoracoscopic approach with cervical anastomosis (McKeown procedure). The abdominal part was performed by totally laparoscopic (group A) or hybrid (group B) hand-assisted gastric tubulization. Clinical parameters, symptoms of reflux, gastric tube evaluated by tomography, post-operative endoscopic findings were assessed and compared between groups. Multivariable analysis was performed. Results: 36 group A and 56 group B, 55 (59.7%) were squamous cell carcinoma and 60 (66.6%) did neoadjuvant chemoradiotherapy. Mean follow-up was 32 months. Group A had more gastric tube diameter (p < 0.001), alimentary stasis (p < 0.001), redundant conformation (p < 0.05) and distant from axial central point of the thorax (p < 0.05); all evaluated by tomography. And also, more symptoms of reflux and gastric empty delay by reflux symptoms index (RSI) (p < 0.001); and numbers of esophagitis grade B and C by upper endoscopy (p < 0.01). After multivariable analysis, intracorporeal (p < 0.001) and diameter more than 4.2 cm (p < 0.01) was related to worst RSI. Conclusion: The intracorporeal gastric tube reconstruction may lead wider gastric tube conformation, which might be related to gastric empty delay, resulting in intense reflux symptoms confirmed by upper endoscopy.